Women in the Mayo Clinic Department of Neurology in its early years. Issue 5 (15th September 2022) - Smith, Kelsey M.; Boes, Christopher J.; Coon, Elizabeth A.
Abstract: The stories of early women physicians in the field of neurology are seldom discussed. Understanding the history behind women in neurology can inform our current practice and uncover the possible origins of gender disparities in academic neurology. Utilizing annual section/department reports and other primary sources, we describe the first women trainees and staff who broke gender barriers to train and work in the Mayo Clinic Department of Neurology. The department was founded in 1913 when Walter Shelden became its first consultant. It was not until the 1950s that a woman completed her neurology training and went on to practice neurology. Throughout the early years of the training program, there were no women on staff, as it was not until the 1970s when the first women were hired as consultants.